Perforated duodenal diverticulum: Surgical treatment and literature review - Costa Simões, V. (2014)
Duodenum is the second most frequent location for a diverticulum in the digestive tract. Complications are rare and perforation was only reported in less than 200 cases. PRESENTATION OF CASE: A 79-year-old female was admitted to Emergency Department with abdominal pain and vomiting for the last 24h. A CT scan was performed and moderated extra-luminal air was identified. During surgery a fourth portion perforated duodenal diverticulum was diagnosed and duodenal resection was performed. DISCUSSION: First reported in 1710, the incidence of duodenal diverticula can be as high as 22%. Nevertheless complications are extremely rare and include haemorrhage, inflammation, compression of surrounding organs, neoplastic progression, cholestasis and perforation. As perforations are often retroperitoneal, symptoms are nonspecific and rarely include peritoneal irritation, making clinical diagnose a challenge. CT scan will usually present extra-luminal retroperitoneal air and mesenteric fat stranding, providing clues for the diagnosis. Although non-operative treatment has been reported in selected patients, standard treatment is surgery and alternatives are diverse including diverticulectomy or duodenopancreatectomy. CONCLUSION: Perforated diverticula of the fourth portion of the duodenum are extremely rare and current evidence still supports surgery as the primary treatment modality.